Linguistic deception of Chinese cyber fraudsters - Tan, Kim Hua; Guilani, Mohammad Abdollahi; Chen, Chenzi (Penerbit Universiti Kebangsaan Malaysia, 2017)
Cybercrimes are on the increase in China and ‘QQ’, an instant messenger platform, is frequently exploited for these crimes. Fraudsters manipulate language to deceive users into revealing their bank accounts or depositing sums in the cheats’ accounts. Employing the theoretical framework that includes Speech Act Theory and Politeness Theory, the researchers attempted to identify the strategies used by such fraudsters. The subjects of this study included 50 interlocutors who had already chatted with different online cheats and had a record of their conversations. The data were collected and analysed on the basis of the type of discourse themes displayed. Findings indicated that the chats displayed various themes like Business Invitation, Money Transfer, Account Hacking and Online Shopping. In addition, the three levels of speech acts of locutionary, illocutionary, and perlocutionary were discernible and most fraudsters did not bother to address face threatening acts. In comparison to hoax email writers, the fraudsters in instant communication regularly came across as more aggressive and imperative, but then softened their diction if victims were not interested to chat with them in real time. The implications of this study lie in the possibility of developing a model for fraudster or cheat discourse structure, thus alerting QQ users in particular of such crimes. Other online instant messenger users will also benefit from this study. Better informed of how cheats manipulate language to present untruth as truth and be alerted of the modus operandi involved in online deception, victims can be saved and the crime curbed. The issue of the victim’s vulnerability and the reasons behind it certainly deserve further linguistic and metalinguistic scrutiny.